Penerapan Model Pembelajaran Creative Problem Solving Dalam Meningkatkan Pemecahan Masalah Matematis - Wariyanti, Astri; Karnasih, Ida; Hasratuddin, Hasratuddin (JURNAL PENA EDUKASI, 2021)
Abstract: Mathematics is one of the important subjects to learn because its existence can help humans to solve various problems in everyday life. One of the roles and tasks of educators in order to maximize student learning opportunities is for students to have mathematical problem solving abilities. This is done so that students can solve problems in their lives. For this reason, educators in the process need to consider a learning model that can encourage students to achieve these abilities, namely the Creative Problem Solving (CPS) learning model. The purpose of this study was to describe the extent to which the application of the Creative Problem Solving learning model in improving problem solving abilities. The research method is a literature review by searching for articles from the database. Articles were searched using keywords that had been determined by the researcher, so 19 articles were found to be analyzed. The results of the studies state that the Creative Problem Solving learning model can improve problem solving abilities. Keywords: creative problem solving; problem solving  Abstrak: Matematika merupakan salah satu mata pelajaran yang penting untuk dipelajari karena keberadaannya dapat membantu manusia untuk memecahkan berbagai masalah dalam kehidupan sehari-hari. Salah satu peran dan tugas pendidik dalam rangka memaksimalkan kesempatan belajar siswa adalah agar siswa memiliki kemampuan pemecahan masalah matematis. Hal tersebut dilakukan agar siswa bisa menyelesaikan permasalahan didalam kehidupannya. Untuk itu, pendidik dalam prosesnya perlu mempertimbangkan model pembelajaran yang dapat mendorong siswa untuk mencapai kemampuan tersebut, yaitu model pembelajaran Creative Problem Solving (CPS). Tujuan penelitian ini adalah untuk mendeskripsikan sejauh mana penerapan model pembelajaran Creative Problem Solving dalam meningkatkan kemampuan pemecahan masalah. Metode penelitian berupa literature review dengan cara mencari artikel dari database. Artikel dicari dengan menggunakan kata kunci yang sudah ditentukan peneliti, sehingga ditemukan 19 artikel untuk dianalisis. Hasil penelitian-penetian menyatakan bahwa model pembelajaran Creative Problem Solving dapat meningkatkan kepampuan pemecahan masalah. Kata kunci: creative problem solving; pemecahan masalah